The environmental factors that influence success of women entrepreneurs : entrepreneurial intention as a mediator - Nur Sha Azelda Hashim; Mohd Rafi Yaacob; Mohd Nazri Muhayiddin (Faculty of Entrepreneurship and Business,UMK, 2015)
– Entrepreneurship typically focuses on identifying opportunities in order to create values for